Larval morphology of genus Megacephala Latreille, 1802 (Coleoptera: Cicindelidae). - Putchkov, Alexander V.; Arndt, Erik (Contributions to Entomology = Beiträge zur Entomologie, 1997)
A description of larval characters of the genus Megacephala Latreille and a larval key to five of the six subgenera are given. The most characteristic larval characters of Megacephala are the Y-shaped gular suture (known from all Megacephalini) and the lack of an oval double sclerite on the prementum. The anterior margin of the clypeus of the subgenus Phaeoxantha is serrated, which is probably the plesiomorphic character state. The subgenus Tetracha includes at least two distinct species groups, which are distinguished by the chaetotaxy of the pronotum and abdomen.